2012
DOI: 10.3329/jbcs.v25i1.11774
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Chromium from Tannery Effluent Using Chitosan-Charcoal Composite

Abstract: Chitosan-charcoal composite was applied as a media to treat tannery effluent. The composite was prepared by a simple solution-evaporation method and the morphology of the prepared composite was characterized by scanning electron microscopy (SEM) and X-ray diffraction (XRD). Adsorption of chromium (Cr) was investigated by varying the contact time between adsorbate (Cr) and composite, pH of solution and dose of composite. The concentration of Cr was determined by atomic absorption spectroscopy (AAS). Removal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 13 publications
0
7
0
2
Order By: Relevance
“…Water quality is determined by some parameters such as bio- were acidified with 0.1 N HCl to maintain its pH at a value of 3.8 -4.0 since it is reported that adsorption is increased with an increase in pH from 2.0 to 4.0 (Siraj et al, 2012). COD of water is another important parameter to measure its quality.…”
Section: Resultsmentioning
confidence: 99%
“…Water quality is determined by some parameters such as bio- were acidified with 0.1 N HCl to maintain its pH at a value of 3.8 -4.0 since it is reported that adsorption is increased with an increase in pH from 2.0 to 4.0 (Siraj et al, 2012). COD of water is another important parameter to measure its quality.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, deprotonated hydroxyl groups can be involved in the coordination with metal ions (Lerivrey, Dubois, Decock, Micera, & Kozlowski, 1986). Chitosan-charcoal composite was applied as a media to treat tannery effluent containing chromium (Siraj et al, 2012). The deacetylated chitosan (HDC) beads, cross-linked HDC-TPP beads, and chemical cross-linked HDC-ECH were used in the adsorption behavior of anionic dye (congo red or direct red 28) and cationic dye (methylene blue or basic blue 9) (Thein Kyaw, Sander Wint, & Myo Naing, 2011).…”
Section: In Treatment Of Industrial Effluentmentioning
confidence: 99%
“…The composite was employed for the adsorption of chromium by various rate, pH and dose of adsorbent. The adsorption capacity was dependent on maximum pH [5]. Magnesium and coconut shell-activated carbon composite was involved to selectively remove the heavy metal ions in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%